TO PERFORM SERIAL ELECTROCARDIOGRAM (ECG) ANALYSES IN PATIENTS WITH SUBTLE ECG CHANGES AND EVALUATE THE PERFORMANCE OF THE FOUR-VARIABLE FORMULA IN DETECTING LEFT ANTERIOR DESCENDING (LAD) CORONARY ARTERY OCCLUSION ON CORONARY ANGIOGRAM - AHMAD, S; SIDDIQUE, MB; KHAN, RU; RANA, MOR; SIDDIQUE, H; MASOOM, M (Biological and Clinical Sciences Research Journal, 2024)
Acute coronary syndrome (ACS) is a critical condition that often presents with symptoms such as ‘chest pain,’ ‘shortness of breath,’ and diaphoresis, signaling a potential underlying coronary artery disease. Among the various coronary arteries, the Left Anterior Descending (LAD) artery is particularly interesting due to its significant role in supplying blood to a large portion of the heart muscle. Objectives: To assess the efficacy of the ‘four-variable formula’ in identifying left anterior descending (LAD) coronary artery occlusion, ‘serial electrocardiogram (ECG) analyses’ should be performed on individuals exhibiting minor alterations in the ‘anterior leads.’ Methodology: ‘This study was a cross-sectional study conducted at the Armed Forces Institute of Cardiology’ (AFIC) from Jan 2023 to June 2023. The primary aim was to ‘evaluate the predictive performance of the Four-Variable Formula in detecting Left Anterior Descending (LAD) coronary artery occlusion’ using serial electrocardiogram (ECG) analyses. Upon presentation, a standard 12-lead ECG was performed on each patient. Serial ECGs were conducted at 30-minute intervals for the first two hours or until a definitive diagnosis was made. Following the ECG analyses, ‘all patients were taken to the catheterization lab for coronary angiography within 24 hours of presentation’. The angiographic results served as the gold standard for diagnosing LAD occlusion. An experienced interventional cardiologist, blinded to the ECG findings, performed and interpreted the angiograms. Results: The study included 360 patients, with a mean age of 62 ±11 years (range 32-80 years). The cohort comprised 219 males (62%) and 141 females (38%). Common risk factors included hypertension (69%), diabetes mellitus (46%), smoking (51%), and a family history of coronary artery disease (29%). Coronary angiography identified LAD occlusion in 139 patients (38%) and no significant LAD occlusion in 221 patients (62%). The results suggested that the Four-Variable Formula could be integrated into routine clinical practice to enhance early detection of significant coronary artery disease, particularly in settings where immediate access to coronary angiography is limited. Future studies with more extensive, multicenter cohorts could further validate these findings and potentially lead to widespread adoption of this predictive tool. Conclusion: Our findings suggest that the Four-Variable Formula holds promise as a non-invasive diagnostic tool in emergency settings, aiding ‘in the early identification of patients at risk’ of significant coronary artery disease. By incorporating the formula into clinical practice algorithms, healthcare providers may expedite triage decisions and facilitate timely interventions, ultimately improving patient outcomes.